Estimation and Study on the Potential of Irrawaddy River Waterway - LI Wenjie; LIU Dan; YANG Shengfa; YANG Wei; LONG Hao (Renmin Zhujiang)
The Irrawaddy River is an important waterway that opens the direct route from southwestChina to the Indian Ocean. Aiming at the development of the Irrawaddy River waterway, thispaper deduces the theoretical formula for the waterway depth based on the hydraulics, river dynamicsand available estimation methods for waterway potential, and estimates the theoretical depth of thewaterway that can be achieved in different sections of the Irrawaddy River by the measured data andempirical parameters.The results show that under the condition of 98% navigation guarantee rate ofthe Irrawaddy River, the minimum waterway development depth from Bhamo to Mandalay, Mandalay toProme, and Prome to Yangon is 2.14 m, 2.58 m and 2.75 m respectively, and the annual navigationcapacity is more than 1.8 billion tons.The research results can provide some theoretical andtechnical support for the development of the Irrawaddy River waterway.